Neonatal abstinence syndrome and infant mortality and morbidity: a population-based study - Lisonkova, Sarka; Wen, Qi; Richter, Lindsay L.; Ting, Joseph Y.; Lyons, Janet; Mitchell-Foster, Sheona; Oviedo-Joekes, Eugenia; Muraca, Giulia M.; Bayrampour, Hamideh; Cattoni, Eric; Abrahams, Ronald (Frontiers in Pediatrics, 2024)
Background: Infant health among newborns with NAS has been understudied. We examined infant mortality and hospitalizations among infants diagnosed with NAS after birth. Methods: All live births in British Columbia (BC), Canada, fiscal years 2004/05-2019/20, were included (N=696,900). NAS was identified from ICD-10 codes; the outcomes included infant death and hospitalizations during the first year of life, ascertained from BC linked administrative data. Generalized Estimating Equations (GEE) models were used to adjust for maternal factors. Results: There were 2439 infants with NAS (3.50 per 1000 live births). Unadjusted for other factors, infant mortality was 2.5-fold higher in infants with vs. without NAS (7.79 vs 3.08 per 1000 live births, respectively) due to increased post-discharge mortality NAS (5.76 vs 1.34 per 1000 surviving infants, respectively). These differences diminished after adjustment: adjusted odds ratio (AOR) for infant death was 0.85 (95% confidence intervals [CI]: 0.52-1.39); AOR for post-discharge death was 1.75 (95% CI 1.00-3.06). Overall, 22.3% infants with NAS had at least one hospitalization after post-neonatal discharge, this proportion was 10.7% in those without NAS. During the study period, discharge to foster care declined from 49.5% to 20.3% in infants with NAS. Conclusion: Unadjusted for other factors, infants with NAS had increased post-discharge infant mortality and hospitalizations during the first year of life. This association diminished after adjustment for adverse maternal and socio-medical conditions. Infants with NAS had a disproportionately higher rate of placement in foster care after birth, although this proportion declined dramatically between 2004/05 and 2019/20. These results highlight the importance of implementing integrated care services to support infants born with NAS and their mothers during the first year of life and beyond, even though NAS itself is not independently associated with increased infant mortality.